Autism through a sensory lens : sensory assessment and strategies - Beaney, Joy (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"The fully revised second edition of this easy-to-use resource introduces the sensory differences autistic children may face, and explores how these differences can affect their ability to make sense of the world. It is invaluable in helping those adults working with autistic children to identify the possible triggers for the child's behaviour and consider it through a sensory lens. Children have varying sensory needs so the book offers both a wealth of enjoyable activities for sensory exploration and play, whilst also providing suggestions for strategies and ideas that can be used at home or in school to create an autism-friendly environment. This book: Highlights the possible link between behaviours that challenge and sensory difficulties for autistic children. Provides practical and accessible resources, helping parents, carers and practitioners to gain a greater understanding of sensory differences. Includes an online assessment with accompanying aids to create a visual representation of the child's sensory needs. With both downloadable and photocopiable resources, this practical guide will be an essential tool for parents, carers and practitioners working with children with autism, enabling them to to create a visual profile of areas of difficulty which can form the basis of personalised strategies and fun sensory activities to support the child"--
OCLC-licensed vendor bibliographic record.
Keywords: Autistic children -- Rehabilitation; Autism in children -- Treatment; Sensory integration dysfunction in children -- Treatment; EDUCATION / Special Education / General